Turkey - Bainbridge, James; Atkinson, Brett; Butler, Stuart; Fallon, Steve; Gourlay, Will; Lee, Jessica; Maxwell, Virginia (Footscray, Victoria, Australia Lonely Planet Publications, 2015)
Offers practical information on accommodations, restaurants, shopping, and unusual sights and activities in Turkey.
At head of title: Lonely Planet.
Includes index.
Keywords: Turkey -- Guidebooks